A Model of Fiction Text Teaching Materials Based on Local Wisdom as an Effort to Improve Reading Literacy in Elementary Schools - Sularno; Mukti Widayati; Nurnaningsih (Universitas Pendidikan Ganesha, 2026)
Teaching materials for learning to read fictional texts in elementary schools have not yet demonstrated how to construct phenomena in everyday life that embody local wisdom. This study aims to analyze the need for developing teaching materials for fictional texts based on local wisdom in reading instruction, test their feasibility and effectiveness in elementary schools worldwide, and evaluate their impact on student learning. The method used is Research and Development (R&D). The selected elementary schools are located in different areas and serve grade IV, with 61 students as subjects in this study. Data were collected through questionnaires, observations, and interviews, then analyzed qualitatively and quantitatively. The results showed that teaching materials for fictional texts based on local wisdom were considered highly feasible, with scores of 88 from the validator, 92 from material and language experts, and 96 from media experts. A limited trial yielded an average student score of 85, which increased to 89.3 in a large-scale trial. These results are supported by statistical testing using a one-way ANOVA, which yielded a p-value of 0.036. Based on the study's results, it was concluded that teaching materials for fictional texts were developed by applying attractive visual design principles, in accordance with learners' background needs in reading. The implications include students' interest in understanding real phenomena through local wisdom, practical and systematic grammar, and the integration of local culture.